OP0233 EFFICACY, SAFETY, AND PHARMACODYNAMIC EFFECTS OF THE BRUTON'S TYROSINE KINASE INHIBITOR, FENEBRUTINIB (GDC-0853), IN MODERATE TO SEVERE SYSTEMIC LUPUS ERYTHEMATOSUS IN A PHASE 2 CONTROLLED STUDY. (2nd June 2020) - Isenberg, D.; Furie, R.; Jones, N. S.; Guibord, P.; Galanter, J.; Lee, C.; Mcgregor, A.; Toth, B.; Rae, J.; Hwang, O.; Lokku, A.; Miranda, P.; et al.
Abstract : Background: Fenebrutinib (GDC-0853, FEN) is an oral, non-covalent, and selective inhibitor of Bruton's tyrosine kinase (BTK) in clinical development for autoimmune diseases. Objectives: This was a randomized, placebo-controlled, multi-center study to evaluate the efficacy, safety, and pharmacodynamic effects of FEN in patients with moderate-to-severe systemic lupus erythematosus (SLE) activity. Methods: Patients who met SLICC or revised ACR SLE criteria, had ≥1 serologic marker of SLE, SLEDAI ≥8, and were on ≥1 standard of care (SOC) therapy were included; patients with renal or CNS involvement, or exposure to B cell depleting or calcineurin inhibitor therapy were excluded. Patients were randomized to placebo (PBO), FEN 150 mg QD, or FEN 200 mg BID, for 48 weeks. A corticosteroid taper was recommended, with burst and taper permitted from Week 0 (W0) to W12 and W24 to W36. The primary endpoint was SRI-4 at W48. Post hoc subgroup analyses were conducted based on patient baseline disease characteristics. Results: This study enrolled 260 patients, with the majority recruited in Latin America, USA, and Western Europe. At W48, the SRI-4 response rates for FEN 150 mg QD and FEN 200 mg BID were 51% (95% CI: -8.5, 21.2; p value 0.37) and 52% (95% CI: -7.3, 22.4; p value 0.34), respectively, compared to 44% for PBO (Table 1 ). Post-hoc analysis showed larger responses in subgroups of patients with higher baseline disease activity (Table 1 ). Safety results were similar between FEN and PBO arms, although more serious adverse events were observed in the FEN 200 mg BID arm. Study discontinuations were balanced across the 3 arms (24-26%). FEN treatment significantly reduced levels of CD19+ B cells, anti-dsDNA autoantibodies, IgG, and a BTK-dependent RNA signature highly expressed in plasmablasts by W48 compared to PBO; C4 levels modestly improved with FEN vs. PBO (Table 2 ). Conclusion: The primary endpoint of SRI-4 for FEN was not met despite evidence of strong BTK target and pathway inhibition. FEN had an acceptable safety profile. Several disease activity subgroups were suggestive of a greater treatment effect on SRI-4 compared to PBO Disclosure of Interests: David Isenberg Consultant of: Study Investigator and Consultant to Genentech, Richard Furie Grant/research support from: AstraZeneca, Biogen, Consultant of: AstraZeneca, Biogen, Nicholas S. Jones Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Pascal Guibord Shareholder of: Roche, Employee of: Roche, Joshua Galanter Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Chin Lee Shareholder of: Genentech/Roche and Eli Lilly, Employee of: Genentech/Roche, Anna McGregor Employee of: Genentech/Roche, Balazs Toth Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Julie Rae Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Olivia Hwang Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Armend Lokku Shareholder of: Roche, Employee of: Roche, Pedro Miranda Consultant of: Study Investigator for Genentech, Viviane de Souza Consultant of: Study investigator for Genentech, Juan Jaller-Raad Consultant of: Study investigator for Genentech, Anna Maura Fernandes Consultant of: Study investigator for Genentech, Rodrigo Garcia Salinas Consultant of: Study investigator for Genentech, Leslie Chinn Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Michael J. Townsend Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Alyssa Morimoto Shareholder of: Genentech/Roche, Employee of: Genentech/Roche, Katie Tuckwell Shareholder of: Genentech/Roche, Employee of: Genentech/Roche